Ectopic Pregnancy During Coronavirus Disease 2019 (COVID-19): To Operate, or Not to Operate. Issue 2 (August 2020) - Hansen, Keith A.; Stovall, Dale W.
Abstract : In patients with coronavirus disease 2019 (COVID-19) infection who have an unruptured ectopic pregnancy, carefully consider the benefits and risks of surgery or medical therapy, especially methotrexate-induced immunosuppression.